Accelerating Electrochemical Reactions in a Voltage‐Controlled Interfacial Microreactor. (1st September 2020) - Cheng, Heyong; Tang, Shuli; Yang, Tingyuan; Xu, Shiqing; Yan, Xin
Abstract: Microdroplet chemistry is attracting increasing attention for accelerated reactions at the solution–air interface. We report herein a voltage‐controlled interfacial microreactor that enables acceleration of electrochemical reactions which are not observed in bulk or conventional electrochemical cells. The microreactor is formed at the interface of the Taylor cone in an electrospray emitter with a large orifice, thus allowing continuous contact of the electrode and the reactants at/near the interface. As a proof‐of‐concept, electrooxidative C−H/N−H coupling and electrooxidation of benzyl alcohol were shown to be accelerated by more than an order of magnitude as compared to the corresponding bulk reactions. The new electrochemical microreactor has unique features that allow i) voltage‐controlled acceleration of electrochemical reactions by voltage‐dependent formation of the interfacial microreactor; ii) "reversible" electrochemical derivatization; and iii) in situ mechanistic study and capture of key radical intermediates when coupled with mass spectrometry. Abstract : An interfacial microreactor was developed to accelerate electrochemical reactions (see picture). Voltage‐controlled acceleration of electrochemical reactions was possible through voltage‐dependent formation of the interfacial microreactor. The electrochemical microreactor can be used for on‐demand electrochemical derivatization and the in situ mechanistic study of electrochemical reactions.